Hide - White, Kiersten (New York : Del Rey, 2022)
"The challenge: Spend a week hiding in an abandoned amusement park and dont get caught. The prize: enough money to change everything. Even though everyone is desperate to win--to seize a dream future or escape a haunting past--Mack is sure she can beat her competitors. All she has to do is hide, and shes an expert at that. Its the reason shes alive and her family isnt. But as the people around her begin disappearing one by one, Mack realizes that this competition is even more sinister than she imagined, and that together might be the only way to survive. Fourteen competitors. Seven days. Everywhere to hide but nowhere to run. Come out, come out, wherever you are"--Book jacket flap.
Keywords: Competition -- Fiction; Amusement parks -- Fiction; Competition -- Fiction; Amusement parks -- Fiction; Thrillers (Fiction); Horror fiction; Paranormal fiction